Bread Wheat Varieties Germination Under Influence of temperature Regimes under lab conditions - Sayran Sardar Hassan; Shaee Adeeb Gharib; Suaad Muhamad Sheikh Abdulla; Kazhal Rashid Ahmad (Kufa Journal for Agricultural Sciences)
To study the temperature effect on germination of common bread wheat varieties, an experiment has been carried out at the college of agricultural engineering sciences, the department of biotechnology and crop science, during the seasons 2018-2019. A factorial experiment was conducted based on a Complete Randomized Design (CRD) with two factors and three replications, and each replication contented 10 seeds. Factor A included four temperature levels (5, 15, 25°C, and room temperature (20-23°C) ), and factor B, included five bread wheat varieties including (Adana, Maaroof, Alla, Shaho-2, Azmar-2). The results found out that the effect of bread wheat varieties highly significant effect on the root length, shoot length, germination percentage, seedling vigor index, and vigor index. The highest value for shoot length and seedling vigor index was recorded by Maroof variety. Effect of low temperature was highly significant different for roots and shoot characters, also for vigor index and seedling vigor index, the best temperature for most of these traits was 25 °C. The effect of the interaction between temperature regimes and varieties was highly significant difference for the root and shoot length characters which were Azmar-2 at 15 °C and Adana at 25°C, while germination percentage and seedling vigor index showed high significance difference in this interaction and the highest rate for seedling vigor index was recorded by Maroof variety at 15 °C, germination percentage recorded %100 for most interactions characters.